Maize Media Enhance the Conidia Production of Entomopathogenic Fungi Lecanicillium lecanii also Its Effective to Control the Weevil Cylas formicarius (Fabricius) (Coleoptera: Brentidae) - Lutfi Afifah; Aulia Corry Aena; Nurcahyo Widyodaru Saputro; Anik Kurniati; Rosalia Maryana; Ani Lestari; Slamet Abadi; Ultach Enri (AGRIVITA, Journal of Agricultural Science, 2022)
The growth of entomopathogenic fungi Lecanicillium lecanii is strongly related to the media in increasing the fungi sporulation, enhancing its effectiveness in infecting target pests. This study aims to obtain L. lecanii propagation media with the highest conidia production, and the increased virulence on Cylas formicarius. The first stage of alternative media selection consists of: Potato Dextrose Agar; maize, rice; bran. The second stage of infectivity of the best alternative media consists of 5 treatments in 5 replications: synthetic insecticide (C+); distilled water (C-); 107 conidia/ml; 108 conidia/ml; 109 conidia/ml. The results show that the best colony growth rate is (1.15 mm) on Maize media, and the highest conidia density is (4.2 x 10⁸ conidia/ml) on Maize media is not significantly different from PDA (1.3 x 10⁸ conidia/ml). The best germination rate is (74.31%) on Maize media, and the highest media weight (1.10 g) on Rice media is not significantly different from maize (1.45 g). The infectivity of L.lecanii affect the mortality of C. formicarius (74%) substantially at a concentration of 109 conidia/ml. The LC50 value obtained is 2.6 x 10⁷ conidia/ml. Thus, maize media can be an alternative medium for mass propagation of L. lecanii.